The Romanian agri-food trade: In a permanent deficit? An analysis of the last two decades - Camelia Gavrilescu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 9th Edition of the International Symposium, November 2018, Bucharest, 2018)
Over the last three decades, the Romanian agri-food trade has shown a permanent deficit, starting with 1990 (since the resumption of imports) and until now, except for two years only. The paper analyses the evolution of the agri-food trade deficit in the main periods (transition, pre-accession, post-accession), its structure by geographical orientation and product groups, as well as the main influencing factors. The results highlight the product groups that have been the main contributors to the deficit all along these years and have remained over time the main import commodities (sugar, meat, vegetables, fruits), those that have passed from negative to positive balance (poultry meat, eggs), as well as those with permanent positive balance (cereals, oilseeds). The changes in the geographical directions of the trade flows through the penetration of new markets and the massive increase in exports have contributed significantly to the reduction of the deficit, but the unfavorable structure of exports (with an important share of lowprocessed products) relative to imports largely results in maintaining the agri-food trade deficit.
Keywords: F14; Q17; 330; agri-food trade deficit; Romania; competitiveness; processed products